Case report: Marked electroclinical improvement by fluoxetine treatment in a patient with KCNT1-related drug-resistant focal epilepsy - Mosca, Ilaria; Freri, Elena; Ambrosino, Paolo; Belperio, Giorgio; Granata, Tiziana; Canafoglia, Laura; Ragona, Francesca; Solazzi, Roberta; Filareto, Ilaria; Castellotti, Barbara; Messina, Giuliana; Gellera, Cinzia; et al. (Frontiers in Cellular Neuroscience, 2024)
Variants in KCNT1 are associated with a wide spectrum of epileptic phenotypes, including epilepsy of infancy with migrating focal seizures (EIMFS), non-EIMFS developmental and epileptic encephalopathies, autosomal dominant or sporadic sleep-related hypermotor epilepsy, and focal epilepsy. Here, we describe a girl affected by drug-resistant focal seizures, developmental delay and behavior disorders, caused by a novel, de novo heterozygous missense KCNT1 variant (c.2809A>G, p.S937G). Functional characterization in transiently transfected Chinese Hamster Ovary (CHO) cells revealed a strong gain-of-function effect determined by the KCNT1 p.S937G variant compared to wild-type, consisting in an increased maximal current density and a hyperpolarizing shift in current activation threshold. Exposure to the antidepressant drug fluoxetine inhibited currents expressed by both wild-type and mutant KCNT1 channels. Treatment of the proband with fluoxetine led to a prolonged electroclinical amelioration, with disappearance of seizures and better EEG background organization, together with an improvement in behavior and mood. Altogether, these results suggest that, based on the proband’s genetic and functional characteristics, the antidepressant drug fluoxetine may be repurposed for the treatment of focal epilepsy caused by gain-of-function variants in KCNT1. Further studies are needed to verify whether this approach could be also applied to other phenotypes of the KCNT1-related epilepsies spectrum.